2015
DOI: 10.1080/03602559.2014.961087
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Degradation of PLCL/nHA Biodegradable Scaffolds

Abstract: We investigated the effect of bioactive nanoparticles on the in-vitro degradation of PLCL and PLCL/nHA composite scaffolds. The concentration of nanohydroxyapatite significantly affected the degradation rate. An increase in the crystallinity of the amorphous portion of the polymer was observed. This increased crystallinity was more pronounced in the pure PLCL samples than in those with more nHA. During the degradation process, we observed the appearance of multiple micropores on the scaffold walls as the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Degradation that is too fast could compromise the mechanical integrity of the scaffold, while if it is too slow, the scaffold would interfere in the correct integration of the regenerated tissue. The scaffold should ideally have a speed of degradation equal to or slightly slower than the growth of the tissue [ 6 , 9 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Degradation that is too fast could compromise the mechanical integrity of the scaffold, while if it is too slow, the scaffold would interfere in the correct integration of the regenerated tissue. The scaffold should ideally have a speed of degradation equal to or slightly slower than the growth of the tissue [ 6 , 9 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their research revealed that both NF-PLLA and nHA/NF-PLLA had a faster significantly degradation rate, due to their much larger SSA, compared to poly( L -lactide). Similarly, Diaz and Puerto (2015) examined the effect of bioactive nanoparticles on the in vitro degradation of nHA/poly(L-lactide-co-ε-caprolactone) (nHA/PLCL) composite scaffolds and found that the rate of degradation was significantly dependent on the concentration of nHA [ 59 ]. At 10%, 30% and 50% of total polymer mass the authors incorporated nHA into PLCL and observed that the rate of degradation of the scaffolds was significantly slower with the increase of nHA content compared to lower nHA concentrations and that of pure PLCL (Fig.…”
Section: Nha/synthetic Polymers Degradationmentioning
confidence: 99%
“…Investigation into the effect of nHA nanoparticles on the degradation of PLCL: A) Profile of Mw versus degradation time for PLC/nHA composite scaffolds; B) Changes of water absorption versus degradation time for PLCL/nHA composite scaffold; C) Scanning electron microscopy imaging of PLCL surface morphology: (a) PLCL after two weeks of in vitro degradation, (b) PLCL/10 wt% nHA after four weeks of in vitro degradation (c) PLCL after six weeks of in vitro degradation, and (d)) PLCL/50 wt% nHA after four weeks of in vitro degradation [ 59 ].…”
Section: Fig (1)mentioning
confidence: 99%
“…Hydroxyapatite (HAP, Ca 10 (PO 4 ) 6 (OH) 2 ), the main inorganic component of bone, has caused considerable interest for bone substitution and regeneration, owing to its strong osteoconductive properties, bone-bonding ability, preeminent biocompatibility and bioactivity [ 11 , 12 , 13 ]. Recently, Lee et al prepared nanofibrous PLGA/Gelatin/HAP scaffolds via an electrospinning method and found that the scaffolds exhibited improved biocompatibility and osteoconductivity compared with the PLGA/Gelatin scaffolds [ 14 ].…”
Section: Introductionmentioning
confidence: 99%